Methodical Approaches to Risk Management in a Regional Commercial Bank - Altukhova, Elena Vladimirovna; Zotov, Vladislav Alexandrovich; Markov, Maksim Aleksandrovich (Economy of Regions, 2016)
The article presents the results of the research of the methodological and information infrastructure of the integrated risk management in a regional commercial bank. Within the study of the general development tendencies of the regional banking services market, the most significant risks for a regional bank are revealed. The analysis is carried out on the basis of the stress testing technique developed at the Plekhanov Russian University of Economics. It is based on a technique of dynamic economic and mathematical modeling with the application of information technologies. The created combination of the methodological and instrumental tools allows to carry out the dynamic scenario analysis of the activity of a commercial bank for the identification of potential risks and for the development of the strategy of financial management reducing the potential risks and leveling the consequences of their realization. The received tool allows during the computer test to watch the predicted dynamics of the condition of the key indicators of the activity of a regional commercial bank changing under the influence of the exogenous regulatory measures and instruments of bank management applied to decrease risk and at the same time to introduce adjustments in the perspective strategy of management. As the result of the analysis, the universal management model of the main bank risks in a regional commercial bank within three alternative scenarios is created. The software product allowing to develop and acquire the practical skills of the students in banking is developed. It also may help to develop the methodological support for the regulation of the organizational procedures of risk management in a regional commercial bank. The received software product may be used in a system of the improving the professional skills, and also for obtaining the expected data in a risk management system in a regional commercial bank.